Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Muhammad Azam (Faculty of Economic & Business Universitas Gadjah Mada, 2011)
NO. Penulis ---- Judul Artikel ---- Halaman 1. Muhammad Azam ---- Comparative Study of The Economic Determinants of Foreign Direct Investment in Pakistan, India and Indonesia ---- 1-9 2. Widigdo Sukarman ---- The Politics of Bank Supervision ---- 10-24 3. Sekar Utami Setiastuti ---- Glancing Meteor Shower Over Indonesia : Volatility Spillovers from A Major Stock Market to Indonesian Stock Market and Currency ---- 25-46 4. Mudrajad Kuncoro ---- The Global Economic Crisis and Its Impact on Indonesia’s Education ---- 47-63 5. Haeryp Sihombing, Moh. Yuhazri Yaakob dan Muchamad Safarudin ---- The Business Perspectives Strategy Towards The TKI (Indonesian Migrant Workers) Market ---- 64-89 6. B. Raksaka Mahi ---- Local Own Revenue Mobilization in Indonesia ---- 90-102 7. Mayanggita Kirana dan Samsubar Saleh ---- Public Sector Efficiency in Indonesia (Fiscal Decentralization Era, 2001-2008) ---- 103-128 8. Nur Arifatul Ulya ---- The Impact of Reddi on Institutions Income : a Social Accounting Matrix Approach ---- 129-138